1987
DOI: 10.1007/bf00637676
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of erythromycin with theophylline

Abstract: We have studied the interaction of erythromycin with theophylline. We gave ten healthy volunteers theophylline as an intravenous loading dose (5 mg X kg-1) over 1 h, followed by a maintenance infusion (0.5 mg X kg-1 X h-1) for 5 h. A second infusion of theophylline was given after 9 days of treatment with 1 g erythromycin base daily, and the concentrations of theophylline were determined during the infusion periods. The concentrations of erythromycin were measured for 8 h, after one week of treatment, and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Many studies have shown that pretreatment with erythromycin produces significant increases in plasma concentrations of clinically important drugs such as immune modulators, 7 HIV antivirals, 8 theophylline, 9 , 10 3‐hydroxy‐3‐methylglutaryl coenzyme A (HMG‐CoA) reductase inhibitors, 11 and benzodiazepines 12 , 13 . However, these studies were performed with varied treatment periods of 2 to 10 days of erythromycin, which may affect the extent of drug interactions via CYP3A inhibition.…”
mentioning
confidence: 99%
“…Many studies have shown that pretreatment with erythromycin produces significant increases in plasma concentrations of clinically important drugs such as immune modulators, 7 HIV antivirals, 8 theophylline, 9 , 10 3‐hydroxy‐3‐methylglutaryl coenzyme A (HMG‐CoA) reductase inhibitors, 11 and benzodiazepines 12 , 13 . However, these studies were performed with varied treatment periods of 2 to 10 days of erythromycin, which may affect the extent of drug interactions via CYP3A inhibition.…”
mentioning
confidence: 99%
“…Numerous compounds that form MI complexes with CYP3A4 have been shown to cause clinically significant drug-drug interactions, e.g. erythromycin [182][183][184][185][186][187], nicardipine [188][189][190], and troleandomycin [177,191,192]. Erythromycin is a weak inhibitor of CYP3A4, but during the N-demethylation of erythromycin, a nitroso intermediate is formed which ligates the heme iron and forms a stable complex which prevents further catalysis by the enzyme.…”
Section: Complexmentioning
confidence: 99%
“…The end result of this type of interaction is a diminished biotransformation of the substrate drug leading to an exaggerated pharmacological effect resembling an overdose of the substrate drug, unless the substrate drug is a prodrug. For example, the ability of erythromycin (an enzyme inhibitor) to reduce the metabolism of theophylline (a drug substrate) can lead to dysrhythmias, tremors, and seizures (189). In the presence of enzyme inhibitors, the toxicities resulting from these types of interactions have contributed to the removal of several widely marketed substrate drugs from the U.S. marketplace, including the cholesterol-lowering drug cerivastatin because of an unusually high incidence of rhabdomyolysis, and both the non-sedating antihistamines astemizole and terfenadine and the gastroesophageal reflux drug cisapride for a number of reports of life-threatening ventricular arrhythmias known as torsades de pointes ( Table 2) (118).…”
Section: Drug Biotransformation (Metabolic) Interactionsmentioning
confidence: 99%
“…Excessive blood levels of tacrine induced by concomitant erythromycin or ciprofloxacin therapy could thus be manifested in excessive cholinergic activity at both muscarinic and nicotinic cholinergic receptors, possibly resulting in excessive salivation, lacrimation and sweating, gastrointestinal hypermotility, bradycardia, pupillary constriction, muscle cramps, and central nervous system excitation/agitation (29). Table 3 lists the potential clinical outcomes of coadministration of erythromycin or ciprofloxacin with some CYP1A2 substrates (24, 29, 189, 195, 221, 227, 231, 247).…”
Section: Adverse Interactions Involving Antibiotic/antifungal Agentsmentioning
confidence: 99%